Low-Grade Myofibroblastic Sarcoma of the Oral Cavity: A Report of Three Cases Illustrating an Emerging Disease in Children - Primali Rukmal Jayasooriya; Chamara Athukorala; Manjula Attygalla; Balapuwaduge Ranjit Rigobert Nihal Mendis; Tommaso Lombardi (MDPI AG, 2021)
Low-grade myofibroblastic sarcoma (LGMS) is a mesenchymal tumor of myofibroblasts that occurs more frequently in adults. A series of three cases is presented to illustrate that LGMS may also occur within the oral cavity in children and adolescents. The first case (Case 1) occurred intra-osseously in the mandible, while the remaining two presented as gingival swellings and were purely restricted to soft tissue (cases 2 and 3). The intra-osseous lesion arose in a 7-year-old girl, whereas the gingival lesions were observed in a 12-year-old girl (Case 2) and a 13-year-old boy (Case 3). Histopathologically, all cases were composed of spindle shaped cells arranged into long fascicles showing mild to moderate degree of nuclear atypia. Ki-67 (MIB-1) proliferation activity was relatively low, amounting to 3-5% in all cases. Immunohistochemically, all cases showed smooth muscle actin (SMA) positivity in spindle cells, while desmin, beta catenin, cytokeratin, and CD34 were negative, resulting in a diagnosis of LGMS. In conclusion, current series of three cases of LGMSs that occurred in the oral cavity in a child and two adolescent patients is presented to highlight an emerging disease that requires additional data for further characterization.